Comparison of Ethinyl-Estradiol Plus Cyproterone Acetate Versus Metformin Effects on Classic Metabolic Cardiovascular Risk Factors in Women with the Polycystic Ovary Syndrome - Luque-Ramírez, Manuel; Álvarez-Blasco, Francisco; Botella-Carretero, José I.; Martínez-Bermejo, Elena; Lasunción, Miguel A.; Escobar-Morreale, Héctor F. (The journal of clinical endocrinology and metabolism, 2007)
Context: Oral contraceptives may worsen the metabolic profile of patients with polycystic ovary syndrome (PCOS), favoring the use of insulin sensitizers in these patients. Objective: The aim of the study was to compare the effects of a contraceptive pill on metabolic classic cardiovascular risk factors with those of the insulin sensitizer metformin. Design: We conducted a randomized, parallel, open-label clinical trial. Setting: The study was conducted at an academic hospital. Patients: Thirty-four consecutive PCOS patients were studied. Interventions: Patients were randomized to oral treatment with metformin (850 mg twice daily) or with the Diane35 Diario pill (35 μg of ethinyl-estradiol plus 2 mg of cyproterone acetate) for 24 wk. Main Outcome Measures: Hyperandrogenism, lipid profiles, and indexes of glucose tolerance and insulin sensitivity were measured at baseline and after 12 and 24 wk of treatment. Results: Diane35 Diario resulted in higher reductions in hirsutism score and serum androgen levels compared with metformin. Menstrual regularity was restored in all the patients treated with Diane35 Diario compared with only 50% of those receiving metformin. Plasma apolipoprotein A-I and HDL-phospholipid levels increased with Diane35 Diario, whereas metformin did not induce any change in the lipid profile. On the contrary, the insulin sensitivity index increased with metformin but did not change with Diane35 Diario. No differences in the frequencies of abnormalities of glucose tolerance and dyslipidemia were found between both treatments. Conclusions: Diane35 Diario appears to be superior to metformin for the control of hyperandrogenism and for the restoration of menstrual regularity in PCOS patients, and it is not associated with any clinically relevant worsening in the classic metabolic cardiovascular risk profile of these women.